1978
DOI: 10.1002/jsfa.2740290806
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preslaughter lairage on serum thyroxine and cortisol levels at slaughter, and meat quality of boars, hogs and gilts

Abstract: Commercial crossbred hogs and gilts, and purebred Landrace boars and gilts were slaughtered after a lairage period of either 2 or 24 h. The meat quality of the carcasses was assessed by measuring the pH of the Longissimus dorsi and adductor muscles at 45 min and 20 hpost mortem. Serum cortisol and thyroid parameters were measured in blood taken at slaughter. The incidence of the pale, soft and exudative (PSE) condition was slightly higher in purebred Landrace pigs killed after a short lairage period than in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
3

Year Published

1980
1980
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 24 publications
1
20
3
Order By: Relevance
“…Based on the results in Table 2, pigs given 3 h lairage showed the lowest cortisol levels, which agrees with Warriss, Brown, Edwards, Anil, and Fordham (1992), who reported that the recovery of cortisol was complete within 2-3 h. However, other authors found decreased cortisol values in pigs held in lairage overnight (Moss & Robb, 1978;Warriss et al, 1998). On the contrary, cortisol levels increased when lairage time was prolonged to 8 h or 24 h in our study, which may be ascribed to increased fighting in these groups as evidenced by progressive skin blemish scores.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on the results in Table 2, pigs given 3 h lairage showed the lowest cortisol levels, which agrees with Warriss, Brown, Edwards, Anil, and Fordham (1992), who reported that the recovery of cortisol was complete within 2-3 h. However, other authors found decreased cortisol values in pigs held in lairage overnight (Moss & Robb, 1978;Warriss et al, 1998). On the contrary, cortisol levels increased when lairage time was prolonged to 8 h or 24 h in our study, which may be ascribed to increased fighting in these groups as evidenced by progressive skin blemish scores.…”
Section: Discussionsupporting
confidence: 92%
“…However, when pigs were subjected to 24 h lairage, pH 24 in BF was 5.91, which is close to the pH value for DFD meat. Moss and Robb (1978) also found an increasing tendency to DFD meat with longer lairage time. The present study showed that 3 h lairage decreased drip loss in both muscles, while extended lairage time did not reduce drip loss further.…”
Section: Discussionmentioning
confidence: 75%
“…The animals given 3 h lairage showed the lowest cortisol levels. Warris et al [29] found that the recovery of cortisol was complete within 2-3 h, but in other works, Warris et al [30] found lower cortisol levels in pigs held and fed in lairage overnight, as did Moss and Robb [22]. On the contrary, in our study a tendency to increase can be seen when lairage time is prolonged to nine hours.…”
Section: Discussioncontrasting
confidence: 64%
“…Although extended feed withdrawal, especially with mixing of unfamiliar pigs, is expected to increase the frequency of DFD pork (Moss and Robb 1978;Warriss and Brown 1985;Murray and Jones 1994;Warriss 1995b;Gispert et al 2000), within the current study, the FW-Piggery treatment had a positive impact by slightly darkening the muscle with very little increase in the tendency toward DFD pork.…”
Section: Muscle Quality Traitsmentioning
confidence: 48%